FROM HEISENBERG TO HEGEL: METAPHYSICAL REFLECTIONS ON QUANTUM PHYSICS - Bueno, Sinesio Ferraz [UNESP] (Univ Fed Reconcavo Bahia, Centro Formacao Professores, 2023)
The rupture established by quantum physics in relation to classical physics led to a redefinition of scientific objectivity, which has since relied on mathematical formalism for the knowledge of wave functions. This conception of a weak objectivity motivated Werner Heisenberg to resort to Plato's idealism to explain the internal constitution of the material world from geometric structures. However, faced with an idealist paradigm incompatible with modern science, Heisenberg conceived that Kant's philosophy would be the most acceptable reference for interpreting quantum phenomena within the empiricist limits of scientific research. This article presents Hegel's idealism of the absolute as a philosophical horizon for a possible overcoming of the rigidity of the Kantian limits, aiming at a metaphysical interpretation of quantum physics.
Keywords: Quantum Physics; Absolute Idealism; Hegel; Metaphysics; Philosophy of Physics